Application Of QRIS Payments On Msmes Business Revenue At Rejang Lebong Regency - Yolanda Destiana; Aswin Aswin (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effectiveness of the Quick Response Code Indonesian Standard (QRIS) as a digital payment instrument in the culinary micro, small, and mediumnenterprises (MSMEs) sector in Rejang Lebong Regency, Indonesia. The main issue addressed in this research is the limited adoption of digital payment systems among local MSMEs, despite the government’s continuous effort to accelerate transaction digitalization through the National Non-Cash Movement. The study seeks to determine the extent to which QRIS contributes to improving transaction efficiency, financial record accuracy, and customer satisfaction in culinary based enterprises. This research employs a qualitative approach with data collected through in-depth interviews and direct observations conducted at five MSMEs : Victoria Mini Resto, Bikin Selero, Tudung Saji, Gulapahit Coffee, and Dapur Kito. The findings reveal that four out of fiveMSMEs 80% perceived QRIS as effective in supporting their operational activities. The effectiveness is evident in the acceleration of payment processes, simplified financial record-keeping, and enhanced customer satisfaction particularly among Generation Z consumers. QRIS was also reported to reduce cash-handling errors, streamline cashier operations, and encourage repeat customer visits. Conversely, one MSME 20%, Dapur Kito, found QRIS less effective due to low consumer familiarity with digital payments and limited digital literacy among its customer base. Overall, the results indicate that the adoption of QRIS is significantly influenced by perceived usefulness, perceived ease of use, and social influence factors. The study concludes that QRIS plays an essential role in promoting transaction efficiency, financial transparency, and the advancement of digital financial inclusion within the culinary MSME sector of Rejang Lebong Regency.